Operational Efficiency as a Mediator in the Relationship Between Digital Payment, Digital Customer Service, and Profitability in Indonesian Insurance Companies - Widyana Lestari; Krisdiana Krisdiana (Transpublika Publisher, 2026)
Backgrounds: InsurTech adoption, encompassing digital payment systems and digital customer service platforms, is growing rapidly in Indonesia's insurance industry, yet empirical evidence on how these digital initiatives translate into profitability through operational efficiency mechanisms remains limited among publicly listed general insurance companies. Objectives: This study examines the mediating role of operational efficiency between InsurTech adoption and profitability in Indonesian general insurance companies, with InsurTech proxied by Digital Payment and Collection System and Digital Customer Service, operational efficiency measured by Expense Ratio, and profitability measured by Return on Equity (ROE). Methodology: Using panel data from 11 general insurance companies listed on the Indonesia Stock Exchange during 2020-2024 (55 firm-year observations), the study applies multiple regression and bootstrapping mediation analysis (PROCESS Macro Model 4). Findings: Digital Payment significantly and positively affects both ROE (H1) and Expense Ratio (H2), and full mediation by Expense Ratio is confirmed (H6), with the indirect effect remaining significant (BootLLCI = 0.0803; BootULCI = 0.2436) while the direct effect becomes insignificant. Digital Customer Service does not significantly influence ROE or Expense Ratio, either directly or indirectly (H3, H4, H7 not supported). Conclusions: Internal process digitalization improves profitability only through operational efficiency, underscoring the importance of prioritizing digital investments that reduce operational costs. Customer-facing digital services, while valuable for service quality and loyalty, do not yet produce measurable short-term financial returns through efficiency channels.